Spot It and Learn It! Word Learning in Virtual Peer‐Group Interactions Using a Novel Paradigm for School‐Aged Children. Issue 1 (27th September 2022) - Levy, Helena; Hanulíková, Adriana
Abstract: We use a novel paradigm to examine the effect of language exposure and variable input on the acquisition of words in primary school–aged children. Children growing up with different languages and foreign or regional accents in their input might benefit from their experience with variability when learning new words from peers with unfamiliar accents. We ask to what extent language and accent experience helps monolingual and bilingual children learn new words in the context of accent variability. Children (aged 7–11 years) played a computerized card game with virtual peers that resembles natural advanced lexical acquisition, during which new words are learned from child speakers and are produced actively in peer‐group interactions. Successful word learning was predicted by the amount of input in regional and foreign accents but not by exposure to other languages (i.e., bilingualism). We discuss how accent experience affects word learning under variable input conditions. Abstract :